1991
DOI: 10.1002/stem.5530090303
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 6 (IL‐6) and its receptor: Their role in plasma cell neoplasias

Abstract: Interleukin 6 (IL-6) is a multifunctional cytokine regulating immune response acute phase reaction and hematopoiesis. IL-6 plays a critical role in B cell differentiation to plasma cells and is a potent growth factor for plasmacytoma and myeloma. Abnormal production of IL-6 has been suggested to be involved in polyclonal plasma cell abnormalities and plasma cell neoplasias. The deregulated expression of the IL-6 gene in transgenic mice resulted in the generation of malignant plasmacytoma. Based on these findin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
46
0
1

Year Published

1992
1992
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(50 citation statements)
references
References 130 publications
3
46
0
1
Order By: Relevance
“…Overexpression of IL-6 in transgenic mice induces polyclonal plasmacytosis (Suematsu et al, 1989), and ± depending on the genetic background of the mice ± plasmacytoma develops eventually (Suematsu et al, 1992). These observations suggested a critical role for IL-6 in plasmacytomagenesis (Hirano, 1991). Consistent with this, it was found that IL-6 is essential for raf/myc plasma cell tumor induction (Hilbert et al, 1995a).…”
Section: Il-6 and Stat3 In Plasmacytomagenesismentioning
confidence: 90%
“…Overexpression of IL-6 in transgenic mice induces polyclonal plasmacytosis (Suematsu et al, 1989), and ± depending on the genetic background of the mice ± plasmacytoma develops eventually (Suematsu et al, 1992). These observations suggested a critical role for IL-6 in plasmacytomagenesis (Hirano, 1991). Consistent with this, it was found that IL-6 is essential for raf/myc plasma cell tumor induction (Hilbert et al, 1995a).…”
Section: Il-6 and Stat3 In Plasmacytomagenesismentioning
confidence: 90%
“…16,27 IL-6-mediated growth and proliferation is mediated by the Ras/Raf/MAPK pathway, a known target for the FTIs. 28,29 To date several FTIs have been evaluated in preclinical and clinical trials, 30 including BMS-214664, L-778123, R115777 (tipifarnib), and SCH-66336 (lonafarnib). Overall, FTIs have been shown to have mild toxicities, but also modest activity with the exception of acute myeloid leukemia (AML).…”
Section: Discussionmentioning
confidence: 99%
“…1A). IL-6 is a proinflammatory cytokine shown to be important for the biology of normal and malignant B cells (10,(31)(32)(33)(34)(35)(36)(37)(38)(39). Characterization of this phenomenon revealed that CCL5-induced IL-6 secretion was accompanied by an increase in IL-6 mRNA levels and promoter activity (Fig.…”
Section: Ccl5 Modulates Il-6 Expression and Secretion In Wm Stromal Cmentioning
confidence: 99%
“…Malignant B cells at various stages of development depend on signaling from the surrounding microenvironment to survive and proliferate within the host and promote chemoresistance (3)(4)(5)(6). Bone marrow stromal cells provide malignant B cells with external signals such as soluble growth factors, antigens, cytokines, and cell-cell interactions (7)(8)(9)(10)(11). Therefore, a better understanding of the crosstalk between malignant cells and stromal cells will be essential for the development of new therapies targeting B cell malignancies.…”
mentioning
confidence: 99%